Enfrentamento e resiliência de cuidadores informais de idosos com demência - Santos, Bruna Rodrigues dos (2021)
Knowing and recognizing positive aspects, which can assist in understanding the best adaptation to the role of caregiver, is an important gerontological investigation path, in a scenario where care for the elderly with dementia becomes a serious public health problem. The main objectives of this study were: to analyze the factors related to resilience and coping in caregivers of elderly people with dementia; compare these variables with a group of non-caregivers; and reevaluate them over a period of one year. This is a longitudinal and exploratory study, with quantitative analyzes. The research was carried out in the coverage area of 19 Family Heath Units in the urban area of the city of São Carlos-SP, with two groups: the first, formed by informal caregivers of elderly people with dementia (n=70) and the second, formed by non-caregivers, matched by sex, age and education (n=70). The instruments used for data collection with the research participants were: questionnaire of sociodemographic and health characterization, Zarit Overload Scale (ZOS), Perceived Stress Scale (PSS), Addenbrooke’s Cognitive Examination – Revised (ACE-R), Coping Strategies Inventory (CSI) an Resilience Scale (RS). The evaluations were previously scheduled and carried out on the participants’ homes. The data were analyzed using descriptive comparative statistics and regression. The results showed: (a) A strong negative correlation between RS and PSS (rho= -0.78; p<0.01) and ZOS (rho= -0.79; p<0.01). (b) The score obtained in the CSI also showed a strong and inversely proportional relationship with the score obtained in the PSS (rho= -0.85; p<0.01) and with the score obtained in the ZOS (rho= -0.86; p<0.01). (c) In the multiple regression model using the RS, the variables overload and stress presented negative coefficients (-0.816 and -1.554, respectively), indicating that when we add a unit on the ZOS or on the PSS, we have a decrease in the variable Resilience. (d) In the multiple regression model using the CSI, the stress variables and the attention and orientation domains of the ACE-R showed negative coefficients (-1.027 and -1.056, respectively), indicating that when adding a unit on the PSS or on the ACE-R attention and orientation, we have a decrease in the Coping variable. (e) The participant’s chance of being a caregiver decreases by 3.7% (OR=0.963) when increasing a unit in the RS and increases by 13.1% (OR=1.131) when increasing a unit in the CSI. That is, the greater the resilience, the lower the chances of being a caregiver. And the grater the coping strategies, the greater the chances of being a caregiver. (f) Caregivers’ perceived stress decreased over time (p=0.039). Therefore, for this sample of participants, the length of care had a positive influence on the care experience, confirming the study hypothesis.